Predicting online feminist engagement after MeToo: a study combining resource mobilization and integrative social identity paradigms. Issue 4 (1st October 2020) - Zhou, Qianying; Qiu, Hongfeng
Abstract : Although the MeToo campaign has been suspended in China, this study examines the conditions under which hashtag feminism against sexual harassment may reemerge. Both the resource mobilization and integrative social identity approaches to social movements are adopted in analyzing the data collected in a cross-sectional survey. The results revealed that female netizens' experience of sexism led to their tendency to expose sexual harassment online by participating in online discussions about MeToo. Moreover, female netizens' perceived injustice and Internet efficacy both directly predicted their online engagement tendency and mediated the relationship between group identity and their tendency to engage online. Because both paradigms have strong explanatory power, the prospect of the hashtag feminist movement against sexual harassment in China is contingent upon two conditions. First, a massive number of female netizens could be mobilized to share their personal encounters online without crossing the "high-voltage line" of online censorship. Second, three psychosocial dynamics—group identity, perceived injustice, and Internet efficacy—could provide the momentum required for feminist engagement.